Point-of-care Quantitative Measure Of G6pd Enzyme Activity - Darnina A.J.; Azlin I.; Azma R.Z.; Alina M.F.; Mimi-Azura A.; Cheah F.C.; Nazarudin S.; Najiah-Ajlaa A.; Malisa M.Y.; Norunaluwar J.; Ainoon O (Faculty of Medicine, Universiti Sultan Zainal Abidin, 2024)
Supplementary 2, 2018 (GG2020)